(untitled) (Applied Biological Research, 2023)
Worldwide there is focus on the development of safflower (Carthamus tinctorius L.) varieties having high seed yield coupled with high oil content. The present study was aimed to evaluate the safflower germplasm mapping panel (SGMP) for major seed yield traits and oil content to improve oil productivity of varieties. SGMP consisting of 200 safflower germplasm accessions and four checks (A-1, PBNS-12, NARI-6, NARI-57) were evaluated for 9 quantitative characters during 2016-17. The distribution of data for phenological characters and seed yield was normal, with the exception for seed size and 100-seed weight. The oil content was positively skewed toward higher values, thus indicating panel homogeneity. The studied traits showed significant variation in the germplasm panel. Seed yield and its related characters had high genotypic and phenotypic coefficients of variation, while oil content showed moderate coefficient of variation. Broad sense heritability and genetic advance over percent mean were high for most traits. The principal component analysis revealed that four components explained 75.3% of total variation. There was a strong correlation between seed yield, capitula plant-1, and number of branches plant-1. Superior accessions for each character were identified over the best check. The safflower germplasm mapping panel had wide range variability for the traits studies, and the best accessions can be used in safflower improvement programme. In terms of seed yield, genotypes A1, EC736504, and GMU6663 performed better. Genotype EC736504 gave higher seed yield and oil content. In terms of seed yield, genotypes A1, EC736504, and GMU6663 performed better; however, genotype EC736504 gave higher seed yield coupled with high oil content. For oil improvement, 26 germplasm lines performed better than the checks.